2018
DOI: 10.1093/nar/gky127
|View full text |Cite
|
Sign up to set email alerts
|

PERK/eIF2α signaling inhibits HIF-induced gene expression during the unfolded protein response via YB1-dependent regulation of HIF1α translation

Abstract: HIF1α (hypoxia inducible factor 1α) is the central regulator of the cellular response to low oxygen and its activity is deregulated in multiple human pathologies. Consequently, given the importance of HIF signaling in disease, there is considerable interest in developing strategies to modulate HIF1α activity and down-stream signaling events. In the present study we find that under hypoxic conditions, activation of the PERK branch of the unfolded protein response (UPR) can suppress the levels and activity of HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 42 publications
1
46
0
Order By: Relevance
“…The YB-1 involvement in translation or stability depends on cellular conditions. For example, with simultaneous unfolded protein response (UPR) and hypoxia, YB-1 fails to stimulate HIF-1α mRNA translation [152]. The authors explain this fact by a decreased YB-1 ability to bind the 5 UTR of HIF-1α mRNA [152].…”
Section: Modulating Activity Of Yb Proteins In Translation and Stabilitymentioning
confidence: 99%
“…The YB-1 involvement in translation or stability depends on cellular conditions. For example, with simultaneous unfolded protein response (UPR) and hypoxia, YB-1 fails to stimulate HIF-1α mRNA translation [152]. The authors explain this fact by a decreased YB-1 ability to bind the 5 UTR of HIF-1α mRNA [152].…”
Section: Modulating Activity Of Yb Proteins In Translation and Stabilitymentioning
confidence: 99%
“…Tests conducted in three different cell lines (cervical and prostate cancer as well as fibrosarcoma) led to the hypothesis that tumor-caused hypoxia most likely induces PKC isoform-dependent HIF-1a accumulations. Cell line studies have shown that the HIF1alpha activation was initiated by the AKT-mTOR and NF-kB cascade [90,91].…”
Section: Hypoxic Modulation Of Carcinogenesis Via Mtor Signalingmentioning
confidence: 99%
“…These enzymes are not designed to be in the cytoplasm, and we reason that this release could result in various stress signals leading to inhibition of HIF-1a accumulation. In addition, late endosomes and lysosomes are targets for misfolded protein degradation, and the release of increased amounts of misfolded proteins may result in PERK activation which has previously been shown to result in HIF-1a inhibition (Ivanova et al, 2018;Jackson and Hewitt, 2016).…”
Section: Discussionmentioning
confidence: 99%